Gender differences in mental health symptoms and risk factors in Australian elite athletes - Simon Rice; Rosemary Purcell; Courtney C Walton; Caroline X Gao; Matt Butterworth; Matti Clements (BMJ Open Sport & Exercise Medicine, 2021)
Objectives To examine gender differences in the reporting of, and contributors to, mental health symptoms.Methods This was a cross-sectional observational study of adult athletes within a national elite sporting system (n=523; women=292;56%), who completed a battery of assessments including measures of mental health and adverse life events. Group differences across a range of scores were examined, followed by gender-stratified bootstrapped linear regression and meta-regression on measures where gender differences were observed.Results Women athletes reported higher rates of mental health symptoms, and lower rates of mental well-being, although there were no differences in general psychological distress or life satisfaction. Women reported experiencing several adverse life events at higher rates than men; particularly interpersonal conflict, financial hardship and discrimination. Low self-esteem was consistently associated with poorer mental health outcomes for all athletes. While a range of factors were associated with poor mental health in men or women athletes, meta-regression suggested that experiencing financial difficulty and social media abuse were more uniquely associated with mental health symptoms in men.Conclusion Gender differences in mental health in elite athletes are apparent. Approaches to increasing well-being are required in elite sport.